1991
DOI: 10.1111/j.1365-2125.1991.tb03868.x
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone concentrations in cerebrospinal fluid after different prednisolone prodrugs.

Abstract: The concentration‐time curves of prednisolone in cerebrospinal fluid (CSF) and plasma were measured following an equimolar i.v. bolus dose of prednisolone phosphate (five patients) and prednisolone phthalate (four patients). Independent of the prodrug administered, the value of the AUC (0.360 min) in CSF was more than three times lower than the corresponding value in plasma. The AUCs of unbound prednisolone in plasma were higher after prednisolone phosphate, than after prednisolone phthalate (68.1 +/− 15.7 vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(8 reference statements)
0
2
0
1
Order By: Relevance
“…Therefore, at the beginning of our treatment of SSNHL and according to the principles of high-dose (pulse-dose) corticoid therapy used by other specialties (neurology, transplantation medicine, etc), we applied similar high doses. Bü hrer et al 31 demonstrated in humans that after intravenous administration of prednisolone, the concentration in cerebrospinal fluid was only approximately one third of the corresponding plasma concentration. One hour after intravenous application of methylprednisolone in the perilymph of guinea pigs, Parnes et al 32 measured only one sixth of the concentration of the corresponding plasma level.…”
Section: Commentmentioning
confidence: 99%
“…Therefore, at the beginning of our treatment of SSNHL and according to the principles of high-dose (pulse-dose) corticoid therapy used by other specialties (neurology, transplantation medicine, etc), we applied similar high doses. Bü hrer et al 31 demonstrated in humans that after intravenous administration of prednisolone, the concentration in cerebrospinal fluid was only approximately one third of the corresponding plasma concentration. One hour after intravenous application of methylprednisolone in the perilymph of guinea pigs, Parnes et al 32 measured only one sixth of the concentration of the corresponding plasma level.…”
Section: Commentmentioning
confidence: 99%
“…Additional references were provided by a search conducted by the Clinical Literature Information department at Merck Research Laboratories that covered a number of other databases besides MEDLINE. The di culties that were reported occurred for drugs with narrow therapeutic windows [29][30][31][32] or for substitutions that were not even 'average' bioequivalent to the original product [33][34][35][36][37]. Imposition of stricter requirements for bioequivalence materially decreased the incidence of reported di culties [28].…”
Section: Clinical Evidencementioning
confidence: 99%
“…ähnlich hohe Dosen (1000 mg/die) appliziert. Bührer et al [30] Neuere Studien haben jedoch gezeigt, dass mit etwa 300 mg Prednisolon alle Kortikoidrezeptoren des Kör-pers besetzt sind [32].…”
Section: Audiometrische Parameterunclassified